Synergy of Interpersonal Intelligence and Organizational Culture in Improving Employee Performance in the Retail Industry in Bandung - Istanto, Gatot; Rachmawati, Mariana (IJSM, 2025)
This study aims to analyze the influence of interpersonal intelligence and organizational culture on employee performance at Factory Outlets in Bandung City. The phenomenon of decreasing number of visitors at several Factory Outlets indicates a challenge in service quality that is suspected to be related to human resource aspects. This study uses a quantitative approach with an explanatory method. Data were collected through questionnaires distributed to 137 respondents from four Factory Outlets, then analyzed using multiple linear regression. The results of the analysis indicate that interpersonal intelligence and organizational culture have a significant influence simultaneously and partially on employee performance. The significance value of the F-test is 0.000 with an F count of 1601.703, while the results of the t-test show a t count value for interpersonal intelligence of 19.319 and organizational culture of 25.939, both of which far exceed the t table. Organizational culture has a dominant influence compared to interpersonal intelligence, but both complement each other in shaping effective work behavior. These findings emphasize the importance of strengthening interpersonal intelligence such as empathy, communication, and teamwork and developing an organizational culture that emphasizes the values of discipline, adaptability, and participatory leadership. The resulting managerial implications include strengthening soft skills training, integrating values into recruitment and performance evaluation, and establishing a consistent work culture as a strategy to increase business competitiveness. This research provides a strategic contribution to human resource management in the customer service-based retail industry